Biosynthesized Platinum Nanoparticles Inhibit the Proliferation of Human Lung-Cancer Cells in vitro and Delay the Growth of a Human Lung-Tumor Xenograft in vivo -In vitro and in vivo Anticancer Activity of bio-Pt NPs- - Bendale Yogesh; Bendale Vineeta; Natu Rammesh; Paul Saili (Korean Pharmacopuncture Institute, 2016)
Objectives: Lung cancer remains a deadly disease with unsatisfactory overall survival. Cisplatin, a standard platinum (Pt)-based chemotherapeutic agent, has the potential to inhibit the growth of lung cancer. Its use, however, is occasionally limited by severe organ toxicity. However, until now, no systematic study has been conducted to verify its efficacy with proper experimental support in vivo. Therefore, we examined whether biosynthesized Pt nanoparticles (NPs) inhibited human lung cancer in vitro and in vivo to validate their use in alternative and complementary medicine. Methods: We evaluated the in vitro and the in vivo anticancer efficiencies of biosynthesized Pt NPs in a subcutaneous xenograft model with A549 cells. Severe combined immune deficient mice (SCID) were divided into four groups: group 1 being the vehicle control group and groups 2, 3 and 4 being the experimental groups. Once the tumor volume had reached 70 ─ 75 mm3, the progression profile of the tumor growth kinetics and the body weights of the mice were measured every week for 6 weeks after oral administration of Pt NPs. Doses of Pt NPs of 500, 1,000 and 2,000 mg/kg of body weight were administered to the experimental groups and a dose of honey was administered to the vehicle control group. The efficacy was quantified by using the delay in tumor growth following the administration of Pt NPs of A549 human-lung-cancer xenografts growing in SCID mice. Results: The in vitro cytotoxicity evaluation indicated that Pt NPs, in a dose-dependent manner, inhibited the growth of A549 cells, and the in vivo evaluation showed that Pt NPs at the mid and high doses effectively inhibited and delayed the growth of lung cancer in SCID mice. Conclusion: These findings confirm the antitumor properties of biosynthesized Pt NPs and suggest that they may be a cost-effective alternative for the treatment of patients with lung cancer.